FACTORS INFLUENCING CARDIOVASCULAR DISEASES AMONG PATIENTS IN THE CARDIOLOGY DEPARTMENT OF A TERTIARY CARE HOSPITAL IN LAHORE: A CROSS-SECTIONAL STUDY (The Research of Medical Science Review, 2025)
To develop and implement effective strategies for the prevention and treatment of cardiovascular diseases (CVD) in older adults, a comprehensive understanding of various CVD risk factors specific to this population is essential. Despite the significance, few studies have focused on older adults. This study aims to assess the prevalence of CVD and its attributable risk factors among older adults in Lahore. Materials and Methods: This prospective, observational study was conducted in the Department of Cardiology at a tertiary care hospital in Lahore. The study aimed to determine the prevalence of lifestyle risk factors among CVD patients attending the hospital. Purposeful sampling was used to select patients who met the study criteria. Adults aged ≥35 years diagnosed with coronary heart disease (CHD) and hypertension (HTN) who attended the hospital voluntarily consented to participate were included. Results: A total of 560 patients were evaluated for CVD risk factors. The mean age of the participants was 52.6 ± 14.8 years, with 57.1% (n = 320) male and 42.9% (n = 240) female. Most patients (44.6%) were in the 40-59 years age group. The diagnosis of CVD often represents a significant disruption in the biopsychosocial balance of individuals, necessitating lifestyle and occupational changes. The new disease requirements impose the adoption of healthier behaviors. Conclusion: The study provides a representative prevalence of CVD and relevant risk factors among the older adult population in Lahore. The high prevalence of CVD risk factors among older adults highlights alarming public health concerns and future health demands. Implementational strategies are required to reduce CVD risk among the elderly through focused promotion of physical activities and early detection of CVDs based on family history.